The Cenozoic leaf morphotypes and palaeoclimate interpretation from the Doi Ton Formation, Mae Sot District, Tak Province, western Thailand - Atiwut Bunlam (2020)
© 2020 Forest Herbarium The Cenozoic palaeovegetation and palaeoclimate of Doi Ton, western Thailand, megaflora are reconstructed based on physiognomic climate analysis, including Leaf Margin Analysis (LMA), Leaf Area Analysis (LAA), Leaf Size Index (LSI), Climate Leaf Analysis Multivariate Program (CLAMP), and systematic descriptions of each leaf morphotype. The leaf fossils were divided into 23 dicotyledonous leaf morphotypes and two unknown leaf morphotypes. The mean annual temperature results from LMA indicate 32.3 ± 1.17°C and CLAMP shows 21.2°C. CLAMP also provides temperature data of a warm month mean temperature (WMMT) of 27.4°C and a CMMT of 14.2°C, which is similar to the present climate. The mean annual precipitation is estimated by LAA to be ~ 125 cm. CLAMP suggests precipitation in the 11 months of growing period was 154.9 cm with the three wettest months having precipitation of 73 cm, widely contrasting with 15.5 cm for the three driest months. The precipitation shows the signal of the monsoon effect. The temperature, precipitation, and LSI mirrored the vegetation of the contemporary Doi Ton area which is a semi-evergreen forest in the tropical zone. The palaeoclimatic parameters of Doi Ton are in good agreement with those of south China and northwest India from the Eocene period and the present-day Mae Sot area. Moreover, the Doi Ton flora also closely matches the humid subtropical modern vegetation of south China. Palaeoclimate and vegetation analysis support an Eocene age estimate for the Doi Ton Formation however further independent age estimates are required to test this working hypothesis.